An Axial and Torsional Percussion Hammer with Considerable Potential to Increase the Drilling Speed of High-Temperature Geothermal Wells. Issue 1 (August 2020) - Zhang, Heng; Ni, Hongjian; Liu, Shubin; Huang, Bin; Liang, Hongjun
Abstract: Geothermal energy is a kind of green and sustainable energy and an essential alternative energy in the future. Improving the drilling speed of geothermal wells is helpful for the efficient exploitation of geothermal resources. Axial & Torsional Percussion Hammer (ATPH) was proposed in this paper for drilling enhancement. ATPH can convert the kinetic energy of the drilling fluid to percussion load, and improve the rock-breaking efficiency of the bit. Because of its mechanical seal design, it can operate efficiently at temperatures over 200 °C, which proves that it can be used in geothermal wells. The large eddy simulation (LES) method is chosen to calculate the percussion load characteristics of the ATPH oscillator, including its main frequency and amplitude. In the field drilling experiments of two high-temperature wells, ATPH showed better ROP enhancement ability and longer working life than PDM. In the well interval drilled by ATPH, the maximum temperature at the well bottom reached 202.54 °C.